Detection of image copy-move forgery using local intensity order pattern - Jing LIN; Tian-qiang HUANG; Ling-peng LIN; Xiao-chen1 LI (Tongxin xuebao)
Copy-move forgery was one of the most simple and common way of image manipulations.To improve the ro-bustness of most existing copy-move forgery detections,a new method based on local intensity order pattern was pro-posed.First,the LIOP feature descriptors were exacted from the inspected image.Then the angular cosine of feature de-scriptors were used to measure the similarity,and the stable matching points were found according to the distance ratio threshold of the nearest neighbor point to the second nearest neighbor.Finally,the space distance of the matching points were calculated to remove the false matching points.Extensive experimental results were presented to confirm that the proposed method is not only able to effectively identify and locate the altered area,but also have high accuracy and ro-bust to scaling,rotation,brightness change and some post-processing,such as Gaussian blur,additive white Gaussian noise and JPEG compression.